2016
DOI: 10.1002/2016ms000656
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation impacts on California's climate with the variable‐resolution CESM

Abstract: The variable‐resolution capability within the Community Earth System Model (VR‐CESM) is applied to understand the impact of irrigation on the regional climate of California. Irrigation is an important contributor to the regional climate of heavily irrigated regions, and within the U.S. there are few regions that are as heavily irrigated as California's Central Valley, responsible for 25% of domestic agricultural products. A flexible irrigation scheme with relatively realistic estimates of agricultural water us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 43 publications
2
28
0
Order By: Relevance
“…Prior research has not quantified the impact of the near-surface feedback, but they do offer insight into methods to deal with it. Recent work by Huang and Ullrich (2016) using a variable resolution atmospheric model to simulate irrigation demonstrates a possible future research direction. Variable resolution climate models allow small scale features, such as localized feedbacks over irrigated regions, to be captured.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research has not quantified the impact of the near-surface feedback, but they do offer insight into methods to deal with it. Recent work by Huang and Ullrich (2016) using a variable resolution atmospheric model to simulate irrigation demonstrates a possible future research direction. Variable resolution climate models allow small scale features, such as localized feedbacks over irrigated regions, to be captured.…”
Section: Discussionmentioning
confidence: 99%
“…If irrigation occurs over large areas, it can have a significant impact on regional climate. Evaporation is increased by irrigation (Leng et al 2013, Lu et al 2015 which cools and moistens the near surface air (Sacks et al 2008, Huang andUllrich 2016) reducing the maximum monthly air temperature by up to 7.5°C in California (Kueppers et al 2007). Because irrigation demand is dynamic, responding to changes in water use, atmospheric conditions, and plant growth, the irrigation induced changes in near surface climate is a feedback on irrigation demand.…”
Section: Introductionmentioning
confidence: 99%
“…With the advent of regional refinement capabilities within select climate models, such as variable‐resolution in the Community Earth System Model (VR‐CESM) (Zarzycki et al, ) and the Model for Prediction Across Scales (MPAS) (Rauscher et al, ; Skamarock et al, ), climate modelers have gained the ability to glimpse into the future of extremely‐high‐resolution global‐scale climate modeling for a fraction of the cost of equivalent resolution global climate models (Leung et al, ; Sakaguchi et al, ). Over the last five years, VR‐CESM has gone from an experimental model to a proven applied research tool for use in regional climate assessment (Gettelman et al, ; Huang et al, ; Huang & Ullrich, ; Rauscher et al, ; Rhoades et al, ; Wu et al, ; Zarzycki et al, ), modeling synoptic‐scale weather systems (Rauscher & Ringler, ) and tropical cyclones (Zarzycki, ; Zarzycki & Jablonowski, ; Zarzycki et al, ), and most recently in regional climate change assessments (Huang & Ullrich, ; Rhoades et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Seasonal synoptic-scale patterns were investigated as part of this work to better understand how shifts Previous studies [14,15] utilizing VR-CESM have demonstrated its competitiveness in studying high-resolution regional climatology when compared to other regional climate models, especially when non-local processes have significant influence on the local climatology. VR-CESM has demonstrated a much 55 better representation of climatology within regions of complex topography, due to the relatively fine regional resolution compared with conventional GCM simulations [16,17,18]. The remainder of the paper is as follows.…”
Section: Introductionmentioning
confidence: 99%